MOBILLE 2019 - Rocca, Sonia (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This MDPI Special Issue contains the conference proceedings of MOBILLE. Hosted by the iconic Lycée Français de New York, MOBILLE was an unprecedented international conference that gathered scholars and practitioners from all over the world in a forum about the impact of new technologies on the learning and teaching of languages. MOBILLE stands for Mobile Language Learning Experience. Language learning occurs in various environments, in dedicated regular classes as well as in those integrating language and subject matter. This Special Issue focuses on how technology-ubiquitous, pervasive and forever changing, shapes the experiences of learners, as well as teachers in primary school, secondary school and beyond. What is mobile is not just the technology, but ultimately the language learning itself.